Improving Students' Letter Recognition Abilities Through The Mystery Box Game At Pembina Dewi Kayangan Kindergarten In The 2024/2025 Academic Year - Ahmi Sapitri, Baiq Dian; Eliyana, Eliyana; Marzoan, Lalu (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to improve students' ability to recognize letters through a mystery box game at TKN Pembina Dewi Kayangan in the 2024/2025 academic year. This is a classroom action research study, with the subjects being 13 children in Group A, consisting of 10 boys and 3 girls. This classroom action research uses the research model developed by Kemmis and McTaggart. The data collection techniques employed include observation, documentation, and interviews. The criteria for this study are individual achievement of 70% and class achievement of 80%.The results of this study indicate that the use of the Mystery Box media game is effective in improving letter recognition skills among children in Group A at TKN Pembina Dewi Kayangan. This is evidenced by the improvement in children's learning outcomes from the pre-cycle stage to Cycle I and a significant increase in Cycle II. In the pre-cycle stage, the classical achievement rate was only 23.07% (3 out of 13 children). After the intervention in Cycle I, mastery increased to 53.8% (7 out of 13 children), and in Cycle II, it increased significantly to 84.6% (1 out of 13 children), indicating that the success indicator had been achieved.